(untitled) (REVISTA SAYWA, 2023)
The development of new methods and/or devices for the diagnosis of diseases, toxic agents, contaminants, and other analytes of environmental, clinical, and biotechnological interest has been the subject of extensive studies. These studies prioritize the various interactions that can occur between the analyte and the molecule responsible for recognition, also known as the bioreceptor. This review presents some strategies that have been developed over the past 20 years for the early detection of human papillomavirus (HPV) infection. Currently, HPV is one of the most common sexually transmitted infections. While the majority of infections are transient and do not cause diseases, some infections can persist and lead to cervical cancer. The most widely used bioreceptors for designing new diagnostic methods are typically synthetic peptides derived from the L1 proteins of the human papillomavirus. The development of an efficient, cost-effective, sensitive, and specific bioreceptor for antibodies generated by HPV is crucial for the advancement of these new diagnostic tools.